Laser Surface Modification of AISI 1025 Low Carbon Steel using Pulsed Nd:YAG Laser for Enhanced Surface Properties - S. N., Aqida; Fauzun, Fazliana; Wahab, Md. Saidin (Trans Tech Publications, Switzerland, 2013)
This paper presents laser surface modification of AISI 1025 low carbon steel for enhance surface hardness properties. An Nd:YAG laser system with pulse mode was used in order to modify 10 mm thick plate surface. Three controlled parameters were laser power, pulse duration and overlap percentage which ranged from 100 to 200 W, 0.4 to 1.0 ms and 50 to 90% respectively. The treated samples was characterised for metallographic study and hardness. Metallographic study was conducted using optical microscope for laser modified layer thickness and grain size. Hardness properties were measured using Vickers indenter. The result show that hardness of laser treated area increased due to fine grain size produced in the laser modified layer. The overlapping rates increase significantly with decreasing laser scanning speed. These findings indicate potential application of low carbon steel in high wear resistant applications through laser surface modification.